Analysis of Tobacco Expenditure Patterns and Health in Five Provinces of Indonesia: Descriptive and Segmentative Approaches - Fauzi , Syafiq Muhammad; Alfian, Zurnan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to identify and analyze community consumption patterns of tobacco products and health expenditures based on 1999 data released by the Indonesian Central Statistics Agency (BPS). The study focuses on five representative provinces in Indonesia: Aceh, Riau, Bengkulu, Bali, and North Sulawesi. Using a descriptive approach and the K-Means Clustering data mining algorithm, this research successfully maps two main consumption patterns that show a negative correlation between tobacco expenditures and the allocation of funds for health needs. Practically, these results provide a cross-regional segmentative overview that can serve as a basis for formulating more responsive public policies, particularly in the areas of health and tobacco consumption control. This study also highlights the importance of integrating historical data with modern analytical approaches to support evidence-based decision-making processes.